أوهام الصّحابة في الرّواية والدّراية (جمعٌ ودراسـةٌ ) - قمودة, حورية; مسيف, قرمية (University of Eloued-جامعة الوادي, 2022)
يتناول البحث مسألة حديثية، تتعلق بأوهام الصحابة في الرواية والدراية، وجاء البحث في مقدمة وفصلين رئيسين وخاتمة، أما الفصل الأول فهو فصل تمهيدي، وفيه مبحثين، يتضمن المبحث الأول التعريف بمصطلحات حدود البحث، أما المبحث الثاني فركز على: مكانة الصحابة، وأسباب وقوع الوهم في روايتهم، وطرق اكتشافه، وأما الفصل الثاني: فهو فصل تطبيقي ويتكون في مبحثين أيضا، خُصِّصَ المبحث الأول: لأوهام الصحابة في الرواية، و خُصِّصَ المبحث الثاني لأوهام الصحابة في الدراية، فكانت أهم النتائج: أن الجيل الأول تميز بخصائص أظهرت فيهم التفوق في الفهم والحفظ والضبط ومع ذلك وقع الوهم في بعض أحاديثهم، وذلك راجع للطبيعة البشرية، وأن الصحابة y كلهم عدول، ولا يقدح في عدالتهم نماذج ناذرة من الأوهام؛ لأن عدالتهم لا تستدعي العصمة، وأن هذا دليل على نزاهة المنهج النقدي الحديثي، فرغم أن هذه الأحاديث التي وقع فيها الوهم، مخرجة في الصحيحين إلا أن ذلك لم يمنع الأئمة من تعليلها، ونسبة الوهم إلى الصحابي يُسقط شبه الاهتمام بالإسناد دون المتن وتقديس الصحيحين. " The research deals with a recent issue related to the mistakes of the Companions in the narration and knowledge (collection and study). The research came in an introduction, two main chapters, and a conclusion. As for the first chapter, it is an introductory chapter, which came in two topics . The first topic included the definition of the research limits terms. The second topic focused on highlighting the status of the Companions, the reasons for the error in their narration, and the methods of its discovery. As for the second chapter, it is an applied chapter that is divided into two topics : The first topic deals with the companions mistakes in narration . The second topic focused on the mistakes of the Companions in knowledge, and the most important results were: that the first generation was distinguished by several characteristics that showed them superiority in understanding, memorization and control. yet some of their hadiths made a mistake, and this is due to human nature, and that the Companions are all just, and they do not undermine these models in their justice rare; Because their justice does not call for infallibility, and this is evidence of the integrity of the hadith critical approach, Although these hadiths in which delusion occurred, are included in the two Sahihs, but this did not prevent the imams from justifying them, and attributing the error to the companion contradicts the interest in the chain of transmission and the sanctification of the two Sahihs "
مذكرة ماستر
Keywords: الصحابي، العدالة، العصمة، الوهم، الفهم، الرواية، الدراية.; Companion, justice, infallibility, error, understanding, novel, know-how.